2009
DOI: 10.1007/s11096-009-9281-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two types of TPN prescription methods in preterm neonates

Abstract: The use of standardized protocols in preterm neonates resulted in more adequate provision of nutrients, weight gain and better blood count profile compared with protocols prescribed by individual physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
(32 reference statements)
3
12
0
3
Order By: Relevance
“…Another example is electronic prescription: Electronic prescription would reduce the RPN of many failure modes listed during the AMDEC (Table 4). Several studies show better nutritional management of patients in care units in which there is electronic prescription [4,22]. In addition, the use of pediatric-specific software for prescribing reduces the risk of errors and helps secure the circuit [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another example is electronic prescription: Electronic prescription would reduce the RPN of many failure modes listed during the AMDEC (Table 4). Several studies show better nutritional management of patients in care units in which there is electronic prescription [4,22]. In addition, the use of pediatric-specific software for prescribing reduces the risk of errors and helps secure the circuit [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is also well known that oxidative stress is related to morbidities associated with prematurity and that vitamin E can be used as an antioxidant defence of the body. 27 Vitamin E is a major free radical scavenger. Tocopherols inhibit lipid peroxidation by scavenging lipid peroxyl radicals much faster than the radicals can react with the fatty acid side chains, thus breaking the chain reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Some recently published studies demonstrated the feasibility of using standardized, even commercial PN in pediatrics and neonatology, although no clear advantage has been demonstrated. [14][15][16][17][18][19] A survey from Israel conducted in 2005 showed that 18 of 25 neonatal intensive care units used commercial PN bags, whereas all others used standardized PN compounded on-site. 20 Standardized commercial PN, albeit theoretically lower in costs and workload, may be inappropriate in several clinical situations, and it forces reliance on the availability of such a product, which, as the recent drug shortage crisis has demonstrated, is not always consistent.…”
Section: Discussionmentioning
confidence: 99%